2015
DOI: 10.1002/jbm.b.33506
|View full text |Cite
|
Sign up to set email alerts
|

Prevascularized silicon membranes for the enhancement of transport to implanted medical devices

Abstract: Recent advances in drug delivery and sensing devices for in situ applications are limited by the diffusion-limiting foreign body response of fibrous encapsulation. In this study, we fabricated pre-vascularized synthetic device ports to help mitigate this limitation. Membranes with rectilinear arrays of square pores with widths ranging from 40 to 200 μm were created using materials (50 μm thick double-sided polished silicon) and processes (photolithography and directed reactive ion etching) common in the manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Further compounding this issue, the fibrous capsule surrounding the implant is quite avascular, 120 preventing efficient glucose delivery to regions inside the collagen capsule. 121 Kumosa et al observed that oxygen levels in the tissue surrounding fully subcutaneous O 2 sensors also decrease over the first several weeks of implantation, 22,107 which may alter glucose sensor response further due to limited O 2 availability (the co-factor for GOx). Of note, the decreased oxygen levels are more likely due to inflammatory cell metabolism and poor vascularization than obstructed diffusion through the capsule.…”
Section: Host Response To Implanted Chemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further compounding this issue, the fibrous capsule surrounding the implant is quite avascular, 120 preventing efficient glucose delivery to regions inside the collagen capsule. 121 Kumosa et al observed that oxygen levels in the tissue surrounding fully subcutaneous O 2 sensors also decrease over the first several weeks of implantation, 22,107 which may alter glucose sensor response further due to limited O 2 availability (the co-factor for GOx). Of note, the decreased oxygen levels are more likely due to inflammatory cell metabolism and poor vascularization than obstructed diffusion through the capsule.…”
Section: Host Response To Implanted Chemical Sensorsmentioning
confidence: 99%
“…Rather, the foreign body capsule increases the tortuosity of the glucose diffusion path from the vasculature to the sensor surface, creating a pronounced lag (on the order of 20–30 min) between glucose concentrations at the sensing surface and corresponding plasma levels. Further compounding this issue, the fibrous capsule surrounding the implant is quite avascular, preventing efficient glucose delivery to regions inside the collagen capsule . Kumosa et al observed that oxygen levels in the tissue surrounding fully subcutaneous O 2 sensors also decrease over the first several weeks of implantation, , which may alter glucose sensor response further due to limited O 2 availability (the cofactor for GOx).…”
Section: Host Response To Implanted Chemical Sensorsmentioning
confidence: 99%